Assesmen Bangunan Gedung Dengan Metode Non Destructive Test (Ndt) Dan Destructive Test (Dt) - Mohammad Junaedy R; Reza Hasrun (Universitas Negeri Makassar, 2023)
Existing building testing is carried out for various purposes that are likely to change the quality of a structure or because the building experiences or is indicated to have errors in workmanship or differences with technical specifications. Ideally, testing is carried out (non destructive) and (destructive test). The buildings used as test locations are the Faculty of Economics UNM, Tellu Cappa Postgraduate UNM, UNM Integrated Laboratory. The observation technique is to collect standards on direct implementation in the field and processing data obtained in the field. Based on the results of observations obtained the implementation method of schimdt hammer test and core drill data processing results schimidt hammer test building Faculty of Economics UNM for all elements obtained an estimated average compressive strength value of 459.4 kg / cm2, UNM Engineering Integrated Laboratory 445.3 kg / cm2, Tellu Cappa Postgraduate UNM 342.9 kg / cm2 While the average compressive strength of core drill samples Faculty of Economics UNM 32.89 MPa, Tellu Cappa Postgraduate UNM 30.06 MPa, UNM Integrated Laboratory 32.86 MPa. In conducting the test, pay attention to the condition of the structural elements or components that will be sampled.